2019
DOI: 10.1155/2019/1659654
|View full text |Cite
|
Sign up to set email alerts
|

Rationales for the Use of Cancer Stem Cells Markers in the Staging of Papillary Thyroid Carcinoma

Abstract: Fine needle aspiration biopsy (FNAB) is a standard procedure for the detection of thyroid nodules malignancy, yet 10-25% of the sample diagnosed may go undetermined or suspicious. The utility of cancer stem cell markers (CSCM) as a differential diagnosis molecular marker in nodules of suspicious decision in FNAB was hypothesized. Papillary thyroid carcinoma (PTC) and thyroid fibroadenoma (TFA) samples were selected to test the hypothesis. The samples employed in this study were from patients who had thyroid hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…In this study, we observed an increased ALDH1A1 expression score with increasing age (although statistically non-significant), with slight male predominance especially in NPT group. This finding coincides with many authors (34)(22) (28). However, a recent study by Kim and Koo has shown no correlation between different gender and age with ALDH1A1 expression in different thyroid tissues (39).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed an increased ALDH1A1 expression score with increasing age (although statistically non-significant), with slight male predominance especially in NPT group. This finding coincides with many authors (34)(22) (28). However, a recent study by Kim and Koo has shown no correlation between different gender and age with ALDH1A1 expression in different thyroid tissues (39).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study has shown that STAT3 activation induced by TESC can upregulate the expression of ALDH1 in non-small cell lung cancer [14], suggesting that TESC can also potentially induce the upregulation of ALDH1. Parallel to our finding, ALDH1A1 displayed notably higher expression in PTC tissues than in normal tissues and had a positive correlation with the tumor stage and size [33]. Similarly, ALDH1A1 knockdown resulted in suppressed proliferative and migratory potential of lung cancer cells [34].…”
Section: Discussionsupporting
confidence: 87%